2012
DOI: 10.1159/000337741
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Adhesion Prevention with a New Barrier: An Experimental Study

Abstract: Introduction: Postoperative adhesion formation remains a major clinical problem. The aim of this study was to test the effect of a new hydrogel on adhesion formation in a rat model. Materials and Methods: A reproducible rat model was used to induce standardized adhesion formation in three experiments. In experiment 1, a cross-linked polyvinyl alcohol (PVA) and carboxymethylcellulose (CMC) hydrogel (PVA/CMC, A-Part®; B. Braun Aesculap, Germany) was tested in different dosages. In experiment 2, PVA/CMC gel was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
(31 reference statements)
0
20
0
2
Order By: Relevance
“…The authors concluded that the application of 4% Icodextrin to extensively de-serosalized surfaces was more convenient when compared to other antiadhesive barriers (22)(23)(24). In contrast to the above findings, Ditzel et al (25) showed that 4% Icodextrin was not effective in significantly reducing the formation of adhesions. Additionally, Bellon et al (26) investigated 4% Icodextrin and also failed to show a significant reduction in IAs.…”
Section: Resultsmentioning
confidence: 93%
“…The authors concluded that the application of 4% Icodextrin to extensively de-serosalized surfaces was more convenient when compared to other antiadhesive barriers (22)(23)(24). In contrast to the above findings, Ditzel et al (25) showed that 4% Icodextrin was not effective in significantly reducing the formation of adhesions. Additionally, Bellon et al (26) investigated 4% Icodextrin and also failed to show a significant reduction in IAs.…”
Section: Resultsmentioning
confidence: 93%
“…Previously, a significant reduction of postoperative adhesion was recorded for PVA/CMC in rats [30,32], rabbits [27,29] and pigs [31], making the material suitable for consideration as an adhesion-prevention agent for hernia meshes. Fujino et al [39] used a 1.5 × 1.5 cm polypropylene mesh directly on the intact peritoneum of rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to promising results regarding functional efficiency, PVA/CMC gel or membrane has been demonstrated to have both the physical and chemical properties necessary to support their use as an adhesion-prevention barrier [26,27,28]. In this case, PVA/CMC gel formed a stable as well as elastic barrier that could be easily and effectively applied [29,30,31] and that yielded a resorption half-life of about 2 weeks, a period that allows sufficient time for the most critical phase of wound healing to occur [32,33]. …”
Section: Introductionmentioning
confidence: 99%
“…Adezyonu azalttığını belirten çalışmalar olduğu gibi başarısız olduğunu belirten çalışmalarda mevcuttur. [2][3][4][5][6] Müller ve arkadaşlarının [21] yaptığı ça-lışmada ise peritonitli olgularda yapışıklığı azaltmadı-ğı gibi daha sık apse gelişimine neden olduğu bildirilmiştir. Çalışmamızda ise sonuçlar değerlendirildiğinde ikodekstrinin yapışıklık oluşumunu belirgin olarak azalttığı saptandı.…”
Section: Discussionunclassified
“…[1] Adezyon önleyici ajan olarak kullanılan %4'lük ikodekstrin solüsyonunun adezyonu önlemede etkin olduğunu belirten çalışmalar olduğu gibi aksi yönde görüş bildiren çalışmalar da vardır. [2][3][4][5][6] Gastrointestinal sistem anastomozları üzerine etkisi konusunda ise literatürde üç adet deneysel çalışmaya ulaşılmıştır. [7][8][9] Çalışmaların ikisinde anastomoz iyileşmesini olumsuz yönde etkilemediği belirtilirken bir tanesinde aksi yönde görüş bildirilmiştir.…”
Section: Bulgularunclassified